PENYELESAIAN PEMBIAYAAN BERMASALAH DENGAN JAMINAN FIDUSIA PADA BANK PEMBIAYAAN RAKYAT SYARIAH DANA MONETER: COMPLETION OF PROBLEM FINANCING WITH FIDUSIAN GUARANTEE IN BPRS - Isnaad, Ainun Putri; Kamsilaniah; Jafar, Juliati (Faculty Of Law Bosowa University, 2021)
The purpose of establishing a Sharia Bank is to mediate between the owner of the fund and the client who needs to obtain funds through agreements and agreed refunds. Through this role, Islamic Banks are recognized to have made many contributions.to.the.country's.economic.and.social.development. But in reality, not all customers have succeeded in returning Islamic Bank funds according to the agreement. There may be a number of problems with financing, which can threaten bank liquidity. This article is intended to explain the problem of Islamic banks and financing methods to solve them.